THE STUDENS’ DIFFICULTIES IN PRESENTING THE ACADEMIC SPEAKING PRESENTATION - Ikhfi - Imaniah; Goziyah - -; Chooi - Heji (Universitas Muhammadiyah Tangerang, 2018)
AbstractThe aim of the research is to observe the activities of the students in academic speaking classroom, to analyze the student’s problem in presenting the academic speaking presentation and to identify the student’s special needs in academic speaking presentation.The method used in this research is field research that is qualitative, while the analysis of the data used descriptive analysis. The focus of the research is on the student’s difficulties in presenting academic speaking presentation.In sum up, most of the students of English Education Study Program of Teachers Training and Education Faculty of Muhammadiyah University are lack of: 1) Goal setting on their academic speaking presentation, 2) Prioritization on what the essential point need to be presented, 3) Self-awareness on themselves, while they present the presentation in front of the audience, 4) Self-motivation while presenting the materials, it connects with self-awareness; if students have improved their self-awareness so they will have a great deal of the information that they need to motivate themselves. In short, the students need to be able to motivate themselves to take action; 5) Planning, most of students are not planning the materials well so they are not able to manage their time to present the academic presentation; and 6) Communication skill, strong communication skills will enable the students to build supportive relationships with the audience while presenting the materials, in fact not all the students have good communication skill.In short, the student’s preparation well made their presentation is good and it also established good communication between the presenter and the audiences.Keywords: Academic Speaking, Presentation, Communication